Flight and digging effort in leaf-cutting ant males and gynes - Silva, E. J. [UNESP]; Camargo, R. S. [UNESP]; Forti, L. C. [UNESP] (Universidade Estadual de Feira de Santana, 2015)
The nuptial flight and nest digging are high intensity activities which consume body reserves. The flight and digging effort was quantified by measuring the carbohydrate and total lipids content in males and females before and after the nuptial flight, and the queen's digging effort during the foundation. The digging effort was quantified by experimentally stimulating the queens to dig a nest - one, two or three consecutive times - compared to the queens that did not dig. The colorimetric method was used to determine the soluble carbohydrates and extraction method of immersion was used to determine the total lipids. The results showed significant loss of carbohydrates and total lipids in males and females after the flight. On average the males contained 0.027 mg of soluble carbohydrates before the nuptial flight, and 0.005 mg after the nuptial flight, and the females contained 0.129 mg of soluble carbohydrates before the nuptial flight, and 0.079 mg after the nuptial flight. For the males the percentage of lipids decreased from 5.27±1.07% to 2.60±0.63% and for females from 36.46±4.86% to 32.62% after the nuptial flight. The digging effort of the queen caused a slight reduction in total carbohydrates, it was without digging 0.054 mg, normal digging 0.055 mg, double digging 0.045 mg (decrease of 20,22 %), and triple digging 0.044 mg (decrease of 20 %) per queen. Based on our results we conclude that the carbohydrate content is the main energetic resource used for the nuptial flight and nest digging, for males and gynes of leaf-cutting ants.
Keywords: Ants; Carbohydrates; Lipids; Social insects